Compensator design for a peak current mode controlled buck converter - Trakuldit, Siripan; Bunlaksananusorn, Chanin (My University, 2019)
This paper presents compensator design for a peak current mode controlled buck converter. Given the closed-loop converter model, the open loop and output impedance transfer functions are derived. Based on the open loop transfer function, the compensator design is carried out to yield the open loop frequency response with a desired gain, crossover frequency, and phase margin. The well designed compensator also results in small output impedance, which is an indicator for good output voltage regulation. Both simulated and experimental results are presented to validate the compensator design.
Keywords: DC-DC converters; Peak current mode control